ANALISIS KETERAMPILAN BERBICARA SISWA KELAS III PADA MATA PELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR ISLAM AL-FALAH 04 JAKARTA BARAT - Lutfi; Nabila Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was made to describe the reading skills of grade III students in Indonesian subjects at Al-Falah 04 Islamic Elementary School, West Jakarta. The purpose of this research is to find out the level of speaking skills of grade III students and to find out students' confidence when speaking in front of the class, to convey their ideas, ideas and opinions. The type of research used in this article is qualitative descriptive. The subjects in this study are 1 Indonesian teacher and 5 grade III students. The techniques used in data collection are observation, interviews, tests, and documentation. The data analysis technique uses an interactive data analysis model. The results of the study showed that students had good speaking skills and there were students who had low speaking skills. Students have low speaking skills, because they are (1) pronunciation, (2) vocabulary, (3) sentence structure, (4) fluency, (5) speech content, (6) body language, (7) comprehension, in these students are still not mastered. A solution for students who have low skills by practicing to improve speaking skills, by paying attention and being active in learning. For students who are good at speaking skills are maintained and improved by continuing to practice.